Surface functionalization of Ag/polypyrrole-coated cotton fabric by in situ polymerization and magnetron sputtering. Issue 23 (December 2019) - He, Shan; Chen, Zhuoming; Xin, Binjie; Zhang, Fuli; Wang, Xiaoying; Liu, Yan; Peng, Aoxin; Yang, Ying
Flexible electronic devices have attracted considerable attention in recent years, and textile fabrics are usually used as the substrates because of their good moisture absorption performance and high flexibility. However, ordinary textile fabrics are electrically insulating, which limits their strain sensing sensitivity. In this study, cotton fabric endowed with high electrical conductivity was prepared by a two-step process of in situ polymerization and direct current (DC) magnetron sputtering. It was firstly modified with a continuous polypyrrole (PPy) thin film by using the in situ polymerization method and then coated with silver (Ag) thin film by using a DC magnetron sputtering system. The experimental results revealed that the resultant Ag/PPy-coated cotton deposited with a sputtering power of 200 W for 25 min has the highest electrical conductivity and its average sheet resistance is 11.7 Ω/sq. Moreover, the Ag/PPy-coated cotton exhibited the advantages of high hydrophobicity, thermal stability, electromechanical performance and washing fastness. Overall, the effective flexibility and high electrical conductivity of the Ag/PPy-coated cotton have been validated effectively and make it one of the promising candidates for preparing electromagnetic shielding and antistatic and smart wearable textile products, especially flexible electronic devices.